Efficient and selective electrosynthesis of 4-aminophenol at circumneutral pH from the electrocatalytic reduction of nitrophenol over the nickel-iron phosphide modified electrode - Ong, Papontee Sae; Huang, Shih Ching; Lin, Chia Yu; Lerkkasemsan, Nuttapol (My University, 2023)
The efficient and sustainable synthesis of 4-aminophenol (4-AP) from the electrocatalytic reduction of 4-nitrophenol (e-NPR) with water as the proton source relies on the development of robust electrocatalysts that readily expedite the kinetics of e-NPR and generate 4-AP with high selectivity at environmentally-benign conditions. In this study, we report on the efficient and sustainable electrosynthesis of 4-AP at circumneutral pH using the micro-structured nickel-iron phosphide modified electrode (CP|microNiFeP). The effects of the iron content of the prepared CP|microNiFeP electrodes as well as electrolysis conditions, including the electrolyte pH, applied potential, and electrolysis duration, on the electrosynthesis of 4-AP were thoroughly examined through a series of controlled-potential electrolyses (CPEs). Under optimal conditions, the CP|microNiFeP electrode exhibited a turnover frequency of 7.25 ± 0.05 h−1 for the generation of 4-AP at 0.0 V vs. RHE and achieved a high 4-NP conversion of 92.29 ± 1.47% with high selectivity for 4-AP generation (SAP:85.77 ± 2.21%) after 8-h CPE at −0.15 V vs. RHE in the H-cell. In addition, the scale-up electrosynthesis of 4-AP with a flow-type electrolyzer was also demonstrated. The 3-h electrolysis using the flow-type electrolyzer resulted in a high 4-NP conversion (93.84 ± 0.84%) with a high SAP (86.32 ± 1.05%). The possible reaction pathways of e-NPR have been proposed, and 4,4′-dihydroxyazobenzene and dimers were identified as the main side products.
Keywords: Electrocatalytic reduction of 4-nitrophenol; Electrochemical deposition; Electrochemical upcycling; Neutral pH; Nickel-iron phosphide